1917 – Die korrumpierte Revolution - Jacob, Frank 1984- (Büchner-Verlag, 2020)
The Russian Revolution of 1917, which in reality consisted of several uprisings, forms the caesura between the »long« 19th and the »short« 20th century and ushered in the so-called »Age of Extremes« (Eric Hobsbawm). Many who had believed in the success of the revolution were bitterly disappointed by the actual developments. Once again, a revolution had not been able to achieve what many had expected, even longed for. The revolutionary uprising of February 1917 ended with its corruption in October of the same year. On the basis of an analytical comparative model, Frank Jacob addresses the question of the process of this corruption and shows whether it was due to an inevitable development of events or rather to the will to power of a few